A new paradigm of quantifying ecosystem stress through chemical signatures. Issue 11 (11th November 2016) - Kravitz, Ben; Guenther, Alex B.; Gu, Lianhong; Karl, Thomas; Kaser, Lisa; Pallardy, Stephen G.; Peñuelas, Josep; Potosnak, Mark J.; Seco, Roger
Abstract: Stress‐induced emissions of biogenic volatile organic compounds (VOCs) from terrestrial ecosystems may be one of the dominant sources of VOC emissions worldwide. Understanding the ecosystem stress response could reveal how ecosystems will respond and adapt to climate change and, in turn, quantify changes in the atmospheric burden of VOC oxidants and secondary organic aerosols. Here, we argue, based on preliminary evidence from several opportunistic measurement sources, that chemical signatures of stress can be identified and quantified at the ecosystem scale. We also outline future endeavors that we see as next steps toward uncovering quantitative signatures of stress, including new advances in both VOC data collection and analysis of "big data."